The Effect of Ethanol Extract Karamunting (Melastoma Malabathricum) Leaf of Ovarian Maturation of Mud Crab (Scylla sp) in Traditional Ponds - Awaludin Awaludin; Nuril Fahrizah; Heppi Iromo; Muhammad Muhammad (Faculty of Science and Technology University Ibrahimy, 2020)
Karamunting is a plant that contains cholesterol. Cholesterol is needed by mud crabs as precursors of reproductive hormones in ovarian development. This study aims to determine the effect of karamunting leaf extract which is injected with mangrove crabs (Scylla sp) on the level of ovarian maturity. The stages of the research included extraction of karamunting leaves using ethanol 70%, experiments by injecting the parent crabs consisting of 3 treatments A (control), B treatment (0.25 mg / g body weight), C treatment (0.5 mg / g body weight) maintained for 20 days by feeding trash fish and measuring parameters including morphological ovarian development, somatic gonad index (GSI), and hepatosomatic index (HSI). The results showed that by giving karamunting extract at the end of the GSI study on control (1.70%), treatment A (5.61%), treatment B (4.24%) while on ovarian development with morphological observation at the end of the study on treatment ovarian control develops in the TKG II phase, A treatment in the TKG V phase while treatment B in TKG IV. This shows that by giving karamunting extract can provide the development of mud crab ovaries.